Application Of Visual Branding In The Development Of Golden Melon Village Educational Tourism, Takerharjo Village, Lamongan Regency - Moh. Dey Prayogo; Avira Citra Paramita, Fransisca Benedicta (International Conference of Innovation and Community Engagement, 2024)
The focus of this community service activity isin 2 areas of problems that have been described, namely problems in the business sector and production sector. In both areas there are several derivative activities, namely creating visual branding ranging from logos to educational tourism package brochures, training on effective and efficient digital marketing strategies, training and mentoring on creating content in social media that focuses on marketing, fulfillment of organic fertilizer production tools, and training on the flow of developing educational tourism in the golden melon village. In the community service activity "Implementation of Visual Branding in the Development of Golden Melon Village Edu-tourism, Takerharjo Village, Lamongan Regency" focused on 3 core stages, namely the creation of visual branding materials, a workshop on building marketing strategies for the development of Takerharjo Village edu-tourism, and a workshop on the use of digital media for marketing partner products. Community service activities carried out by the service team were welcomed by partners in this case the management of UD. Halim Sejahtera and the community who were involved as managers in the company. Through this service activity, it has helped partners in building more modern marketing activities through the development of social media and tools that also support the increasing production of golden melon